Peningkatan SDM UMKM Melalui Pengayaan Packaging Produk di Kecamatan Jombang Kota Cilegon - Arum Wahyuni Purbohastuti; Farah Putri Wenang Lusianingrum; Asmi Ayuning Hidayah; Didik Aribowo; Desmira (Universitas Lancang Kuning, 2021)
The number of Micro, Small and Medium Enterprises (MSMEs) in the city of Cilegon has decreased significantly from 2016 to 2019 amounting to 34,870. The micro and small businesses that are assisted by Posyantek Al-Ikhlas still have problems in developing their product management. On average, MSME actors do not yet master the knowledge of packaging. From these problems, it is necessary to enrich skills regarding packaging with methods training accompanied by mentoring. This training and mentoring program is expected to improve the skills of MSME players in packaging so that they can add value to products and can compete in modern markets. This program will be implemented in four stages including (1) socialization, (2) preparation, (3) implementation of activities, and (4) monitoring and evaluation.